(untitled) (Atlas Journal of Biology, 2017)
The legume tree Pongamia pinnata (also called Millettia pinnata) is a non-food crop that can grow on marginal land not destined for the cultivation of food crops. It is an important candidate for the production of biofuel (bio-oil, biodiesel and aviation biofuel) from its oil-rich seeds. An important trait is its ability to grow in marginal, nitrogen-limited soils. This growth ability is attributed to the nitrogen-fixation activity of root nodules. Cutting both cotyledons in halves had little effect on shoot dry weight, nodule number and weight per plant at 8 weeks. These parameters were reduced when both cotyledons were removed; plants were visibly yellow. Surprisingly when no nutrients were supplied and with both cotyledons intact, plants grew as well as those with nutrients. To isolate rhizobial inoculants from soil, samples were collected from Meandu Mine, a coal-mining site near Kingaroy, Queensland (Australia), where pongamia is currently grown to rehabilitate the soil. Pongamia nodules were also collected from Mt. Coot-tha Botanic Gardens (Brisbane), where pongamia was introduced decades ago. Established ‘Baiting technique’ and ‘One-drop-one-nodule technique’ were applied to isolate potential rhizobia from the soil samples and nodules. All isolates were screened and characterised for symbiotic effectiveness and nitrogenase activity. A total of 21 putative rhizobial samples were isolated – five from soil samples and 16 from pongamia nodules. Out of these iso lates, seven were slow-growers while 14 were fast-growers. These isolates were coded as PR-UQ. Among the isolates, the fast-growers PR-UQ-03 and PR-UQ-05 were considered as the superior strains compared to the slow-growers PR-UQ-01 and PR-UQ-04, which were more effective than the rest of the isolates. The new isolates enhanced nodule number, shoot length and total plant dry weight and resulted in better plant growth than the available Bradyrhizobium japonicum strains CB1809, USDA110 and CB564. Acetylene reduction assay (short term) and Nitrogen Difference Analysis (long term) further confirmed that pongamia fixed more nitrogen upon inoculation with these rhizobia. Based on 16S rDNA sequence analysis, PR-UQ-01 and PR-UQ-04 are closely related to Bradyrhizobium elkanii and Bradyrhizobium pachyrizi, while PR-UQ-03 and PR-UQ-05 are both related to Rhizobium mesoamericanum. Cotyledons supply the seedling with nutrients for a considerable period of early seedling growth. The newly isolated, fast-growing rhizobia PR-UQ-03 and PR-UQ-05 and the slow-growing PR-UQ-01 and PR-UQ-04 are related to Rhizobium and Bradyrhizobium species and aid in the nodulation, nitrogen fixation and seedling/sapling growth of Pongamia pinnata.